Dynamic Behavior of Materials, Volume 1 Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom (Conference Proceedings of the Society for Experimental Mechanics Series, 2011)
Dynamic Behavior of Materials, Volume 1: Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics, the first volume of six from the Conference, brings together 71 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Materials Science, including papers on Composite Materials, Dynamic Failure and Fracture, Dynamic Materials Response, Novel Testing Techniques, Low Impedance Materials, Metallic Materials, Response of Brittle Materials, Time Dependent Materials, High Strain Rate Testing of Biological and Soft Materials, Shock and High Pressure Response, Energetic Materials, Optical Techniques for Imaging High Strain Rate Material Response, and Modeling of Dynamic Response.